Innovation Platforms Practices for Improving Sustainable Intensification in Several Countries and Its Implication to Indonesia: An Integrative Review of Agricultural Innovation Systems - Winda Anestya Ayunda; Indah Purwaningsih; Lutfah Ariana; Husein Avicenna Akil (STI Policy and Management Journal, 2021)
The unsuccessful implementation of Innovation Platforms (IPs) occurs frequently, leading to missed opportunities where improvements could have been made on various aspects of a Sustainable Intensification. This integrative review aims to report research on the scope of productivity innovation, Natural Resource Management (NRM) innovation and institutional innovation of IPs to achieve sustainable intensification in several countries. A comprehensive database search using the search term through a range of electronic database, including Google Schoolar and Scopus from the earliest retrievable records of each database to June, 2020. The search terms used in review were “innovation platforms” and “sustainable intensification”. A total of 9 studies were included in the review.  Based on the result, we propose modifications to the framework to assess both the implementation and evaluation of IPs in Indonesian agriculture systems. We also reflect on some challenges and opportunities for further research and policy- and -development investments in sustainable intensification.